Epigenetics, ovarian cell plasticity, and platelet-rich plasma: Mechanistic theories - E Scott Sills; Samuel H Wood (Bioscientifica, 2022)
Ovarian platelet-rich plasma (PRP) is claimed to restore the fertility potential by improving reserve, an effect perhaps mediated epigenetically by platelet-discharged regulatory elements rather than gonadotropin-activated G-protein coupled receptors, as with stimulated in vitro fertilization (IVF). The finding that fresh activated platelet releasate includes factors able to promote developmental signaling networks necessary to enable cell pluripotency tends to support this theory. The mechanistic uncertainty of intraovarian PRP notwithstanding, at least two other major challenges confront this controversial intervention. The first challenge is to clarify how perimenopausal ovarian function is reset to levels consistent with ovulation. Perhaps a less obvious secondary problem is to confine this renewal such that any induced recalibration of cellular plasticity is kept within acceptable physiologic bounds. Thus, any 'drive' to ovarian rejuvenation must incorporate both accelerator and brake. Ovarian aging may be best viewed as a safeguard against pathologic overgrowth, where senescence operates as an evolved tumor-suppression response. While most ovary cells reach the close of their metabolic life span with low risk for hypertrophy, enhanced lysosomal activity and the proinflammatory 'senescence-associated secretory phenotype' usually offsets this advantage over time. But is recovery of ovarian fitness possible, even if only briefly prior to IVF? Alterations in gap junctions, bio-conductive features, and modulation of gene regulatory networks after PRP use in other tissues are discussed here alongside early data reported from reproductive medicine.